PENGARUH STRATEGI PEMASARAN TERHADAP KEPUASAN KONSUMEN DI CAFE SABA DESA HUTARIMBARU KECAMATAN PANYABUNGAN SELATAN KABUPATEN MANDAILING NATAL - Muhammad Ali Hasan Lubis; Muhlisah Lubis, Muhammad Ardiansyah (BORJUIS: JURNAL OF ECONOMY, 2025)
Muhammad Ali Hasan Lubis, 20090030. The Influence of Marketing Strategy on Consumer Satisfaction at Cafe Saba, Hutarimbaru Village, Panyabungan Selatan District, Mandailing Natal Regency, This research aims to determine the influence of marketing strategies on consumer satisfaction at Cafe Saba, Hutarimbaru Village, Panyabungan Selatan District, Mandailing Natal Regency. The sample used was 100 respondents using the Accidental Sampling method. By using a simple linear regression analysis method. The research results show that marketing strategy has a positive and significant effect on consumer satisfaction with a significance value of 0.000<0.05. The resulting coefficient of determination is 0.445, which means that 44.5% of changes in consumer satisfaction variables are explained by changes in marketing strategy variables, while the remaining 55.5% are explained by other variables not included in this research.